Prevalence of Coccidiosis in Free-Range Chicken in Sidi Thabet, Tunisia - Khaled Kaboudi; Sajid Umar; Muhammad Tanveer Munir (Scientifica)
Background. Enteric diseases are an important concern to the poultry industry and coccidiosis is imposing a significant economic burden worldwide. Objectives. The main goal of the present study was to investigate the prevalence of coccidiosis in free-range chicken in Sidi Thabet, northeast Tunisia. Methods. Six hundred and thirty free-range chickens along with fecal samples were collected from 15 flocks in this region and two hundred chickens were found positive for oocysts of Eimeria spp. Intestines were dissected and examined for macroscopic lesions. The mucosa of small intestine and the caeca were examined for the presence and identification of parasitic forms using parasitology methods. The mean lesion scores were usually low (<2+) in different intestinal portions of different types of chicken and high scores (>2+) were attributed mainly to the caeca. Results. The overall rate of coccidiosis was 31.8%: E. tenella (61.5%), E. maxima (12%), and E. acervulina (1.5%). Mixed Eimeria species infection was observed with overall prevalence 26.5%. There was a statistically significant difference (P<0.05) among infection rates, age groups, season, diarrhea, and type of chicken. Conclusion. This is the first report of coccidiosis rate in free-range chicken in this region. Further additional studies are needed to develop better preventive measures against coccidiosis in the country.